Jejak Tinggalan Peralatan Obsidian Temuan Terbaru di Kawasan Danau Bandung Purba - Nurul Laili (Badan Riset dan Inovasi Nasional (BRIN), 2022)
The City of Bandung and its surrounding, was once a lake known as Bandung Purba Lake in the past. The current form is known as the